ANALYSIS OF BANK PAYMENT CARDS MARKET IN UKRAINE AND PROSPECTS OF ITS DEVELOPMENT (Economics and region, 2017)
UDC 336.717 Nelia Volkova, Ph.D, Associate Professor of the Finance and Banking Department. Poltava National Technical Yurii Kondratyuk University. Kateryna Gogolyeva, Student. Poltava National Technical Yurii Kondratyuk University. Analysis of bank payment cards market in Ukraine and prospects of its development. The current state of bank payment cards market in Ukraine and the main prospects of its further development have been analyzed in the article. The general characteristics of the payment cards development have been determined. The bank operations problems, associated with payment cards have been investigated, as well as the ways to overcome them.Keywords: payment card, bank payment card market, issuing bank, non-cash payments, bank operations.